Pengaruh Pembelajaran Daring Terhadap Efektivitas Belajar Siswa di SMK Pariwisata Bina Satya Mandiri Sukabumi - Tryas Syambogha, Al Luts; Sukriadi, Erie Hidayat; Lesmana, Andhika Chandra (Manajemen dan Pariwisata, 2024)
This research aims to determine the process of implementing online learning as well as to determine the effectiveness of student learning and to find out whether there is an influence between online learning and the effectiveness of student learning at the Bina Satya Mandiri Tourism Vocational School, Sukabumi. In this research the author used descriptive and verification methods with a quantitative approach and data collection techniques, namely observation, interviews, questionnaires and literature studies. The results of the research show that the implementation of online learning at the Bina Satya Mandiri Tourism Vocational School, Sukabumi, is going quite well, the effectiveness of student learning is going very well and there is a positive and significant influence between online learning on the effectiveness of student learning at the Bina Satya Mandiri Tourism Vocational School, Sukabumi.